Knowledge, Attitude, And Factors Affecting Human Papilloma Virus Vaccine Uptake Among Female Undergraduate Students In Public Tertiary Institutions In Lagos State Nigeria. - Elile Monisola Okoka; Joshua Olufisayo Odeyemi; Mariam Ajoke Olu-Ajayi (University Library System, University of Pittsburgh, 2023)
BACKGROUND: Human Papillomavirus is responsible for about 99% of all cervical cancers. Cervical cancer remains a leading cause of morbidity and mortality in women from Low and middle-income countries. Vaccination against human papillomavirus (HPV) is an effective way to prevent the disease, however, uptake remains low in Nigeria. This study aimed to assess the knowledge, attitudes, and factors affecting Human papillomavirus vaccine uptake among female undergraduate students in public tertiary institutions in Lagos State, Nigeria. METHODS: This was a descriptive cross-sectional study. A multistage sampling method was used to select 355 female undergraduate students from Lagos State University and the University of Lagos. Data was gathered using a self-administered structured questionnaire. Data analysis was done using Epi info version 7 statistical software and Chi square was used to test for statistical significance. RESULTS: There were 355 respondents giving a response rate of 100%. The responders' average age was 23 years old. 63.4% and 61.3% had heard about cervical cancer and cervical cancer screening respectively. Only 27.6% had heard of Human Papilloma virus vaccine. While most of the respondents (53.8%) had poor overall knowledge of cervical cancer, majority had a positive attitude towards cervical cancer prevention and screening (80.8%). Only 1.1% of the respondents had received the HPV vaccine, and a lack of awareness about the vaccine was the most commonly reported barrier to uptake (64.7%). Also, only 3.7% had ever done a cervical cancer screening and the most commonly reported reason was "Fear of bad result"(31%). There was no association between overall knowledge of cervical cancer and uptake of cervical cancer screening (p=0.08). CONCLUSION: In conclusion, despite the positive attitude towards cervical cancer prevention and screening, HPV vaccine uptake remains low among young women in this population, and knowledge about the vaccine is lacking. Increasing awareness of the link between HPV and cervical cancer and promoting the vaccine as a safe and effective method of prevention, may help to increase uptake.